2020
DOI: 10.1080/14790718.2020.1766051
|View full text |Cite
|
Sign up to set email alerts
|

Translanguaging and multimodality in workplace texts and writing

Abstract: Professionals working in international companies in Sweden are expected to speak, read, and write in Swedish and English in their daily work. This article discusses professional writing in different languages. Through the use of methods from linguistic ethnography, we aim to enrich the understanding of workplace literacy by studying writing and texts in multilingual business contexts. Our results show that professionals are expected to navigate between a translanguaging mode and a more monolingual mode in ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…Yllätyksenä tapahtunut avaintapahtuma muutti primäärivuorovaikutuksen sekundäärivuorovaikutukseksi (Scollon & Scollon 2004) ja aiheutti Pekalle huolta kielellisen resurssin riittämisestä uudessa tilanteessa. Esimies-alaissuhteen vuorovaikutuksessa työntekijä voi herkemmin kokea vieraalla kielellä kommunikoidessaan epävarmuutta kielellisistä resursseistaan, vaikka sitä ei muussa yhteydessä esiintyisikään (Jonsson & Blåsjö 2020). Kun identiteetti ymmärretään vuorovaikutuskontekstissa kielenkäytön avulla tuotetuksi itsensä asemoinniksi, jonka tavoitteena on tulla tunnustetuksi ja hyväksytyksi yksilönä (Gee 2000), siitä on johdettavissa, miksi Pekka päätyi niinkin vahvaan avaintapahtumaan kuin työpaikan vaihtamiseen kokonaan toiseen yritykseen (esimerkki 3).…”
Section: Vuorovaikutushistorian Avaintapahtumatunclassified
See 1 more Smart Citation
“…Yllätyksenä tapahtunut avaintapahtuma muutti primäärivuorovaikutuksen sekundäärivuorovaikutukseksi (Scollon & Scollon 2004) ja aiheutti Pekalle huolta kielellisen resurssin riittämisestä uudessa tilanteessa. Esimies-alaissuhteen vuorovaikutuksessa työntekijä voi herkemmin kokea vieraalla kielellä kommunikoidessaan epävarmuutta kielellisistä resursseistaan, vaikka sitä ei muussa yhteydessä esiintyisikään (Jonsson & Blåsjö 2020). Kun identiteetti ymmärretään vuorovaikutuskontekstissa kielenkäytön avulla tuotetuksi itsensä asemoinniksi, jonka tavoitteena on tulla tunnustetuksi ja hyväksytyksi yksilönä (Gee 2000), siitä on johdettavissa, miksi Pekka päätyi niinkin vahvaan avaintapahtumaan kuin työpaikan vaihtamiseen kokonaan toiseen yritykseen (esimerkki 3).…”
Section: Vuorovaikutushistorian Avaintapahtumatunclassified
“…Esimerkit osoittavat, että vuorovaikutusjärjestykseen vaikuttavat moninaiset seikat toimijahistoriasta fyysisiin olosuhteisin. Eri kulttuuriympäristöjen kasvatit tunnistavat toistavansa omalle työkulttuurilleen tyypillistä vuorovaikutusjärjestystä (Jonsson & Blåsjö 2020). Sen lisäksi, että suomalainen toimija asemoi itse itseään (esimerkki 14), myös saksalainen kollega asemoi haastateltavaa tiettyyn positioon.…”
Section: Työyhteisön Jäsenten Keskinäiset Suhteetunclassified
“…In the direction touched upon above, from the study of discrete, established genres, there are also studies that examine the roles and mutual relationships between spoken interactions and written texts in organizational practices, such as risk analysis (Karlsson 2009b) and organizational planning (Honkanen and Nissi 2014). These studies have shown that communicative processes at workplaces are often based on multimedial practices and complex intertextual chains that use both written and spoken language (see also Jonsson and Blåsjö 2020;Karlsson and Makkonen-Craig 2014). Some works have also analysed the very position of "talk" in contemporary workplaces, paying attention to new kinds of discursive devices that aim at "discoursing" across various professional and organizational boundaries, and by so doing, oblige workers to renegotiate their professional knowledge and identity (Iedema and Scheeres 2003).…”
Section: Written and Spoken Communicationmentioning
confidence: 99%
“…Creese et al 2017;Zhu et al 2015) and on how professionals in their writing processes often use several languages (e.g. Jonsson and Blåsjö 2020). In studies about multilingualism, questions about language policies, language ideologies, and the statuses of different languages often become relevant (e.g.…”
Section: Intercultural Communication and Multilingualismmentioning
confidence: 99%
“…Digital literacy is often described as the ability to use digital media in everyday, goal-directed, activities in work, school, or leisure real-life situations (Martin, 2006;Jones & Hafner, 2012;Barton & Lee, 2016). Such situations often entail a high degree of complexity when it comes to social roles and agencies, as well as different material artefacts, and different places, i.e., sociomaterial aspects (Wilber, 2008;Kress, 2010;Björkvall & Karlsson, 2011;Bhatt & de Roock, 2013;Jonsson & Blåsjö, 2020). This line of research is often in agreement that human actions and artefacts (e.g.…”
Section: Introductionmentioning
confidence: 99%